Diploma Mills : How For-Profit Colleges Stiffed Students, Taxpayers, and the American Dream - Angulo, A. J. (Book collections on Project MUSE., 2016)
"In this provocative history of for-profit higher education, historian and educational researcher A.J. Angulo tells the remarkable and often sordid story of these 'diploma mills, ' which target low-income and nontraditional students while scooping up a disproportionate amount of federal student aid. Tapping into a little-known history with big implications, Angulo takes readers on a lively journey that begins with the apprenticeship system of colonial America and ends with today's politically savvy $35 billion multinational for-profit industry. He traces the transformation of nineteenth-century reading and writing schools into "commercial" and "business" colleges, explore the early twentieth century's move toward professionalization and progressivism, and explains why the GI Bill prompted a surge of new for-profit institutions. He also shows how well-founded concerns about profit-seeking in higher education have evolved over the centuries and argues that financial gaming and maneuvering by these institutions threatens to destabilize the entire federal student aid program. This is the first sweeping narrative history to explain why for-profits have mattered to students, taxpayers, lawmakers, and the many others who have viewed higher education as part of the American dream. Diploma Mills speaks to today's concerns by shedding light on unmistakable conflicts of interest long associated with this scandal-plagued class of colleges and universities"--Jacket